5 Surface Electrocardiogram Signals Variation with Posture in Normal Adults and in Adults with Congenital Heart Disease and its Clinical Implication. (31st May 2014) - Zeb, Mehmood; Roberts, Paul; Yue, Arthur; Morgan, John
Abstract : Introduction: Ambulatory cardiac monitoring devices and the novel subcutaneous ICD (SICD) sensing algorithms are based on the surface electrocardiograms (ECGs) parameters for detection and discrimination of arrhythmias. However the impact of posture, cardiac morphologies (normal and congenital heart diseases), and electrode placement on these parameters are not known. Aim: To determine the impact of posture (standing, sitting, supine, left lateral, right lateral) and bipolar electrode location (LI, LII, LIII), cardiac morphologies (normal, TOF, TGA, SVP) and gender on R-wave amplitude, T-wave amplitude, R/T ratio, QRS, QTc, Tpeak-end duration. Method: 720 bipolar vectors were collected in a set of three lead (LI, LII, LIII) transcutaneous ECGs at gain 10, at a speed 25mm/sec from three location of SICD sensing arrays in 6 postures from 40 patients including 10 normal controls, 10TOF, 10 SVP, 10 TGA. The ECGs were digitally measured and analysed using repeated-measures ANOVA and Post hoc Helmert contrast pair wise analysis with Bonferroni adjustment. A p value of less than 0.05 was considered significant. Results: The mean R-wave amplitude was significantly smaller in LI than LIII (p = 0.025), and right lateral posture in comparison to left lateral posture (p = 0.02). The T-wave amplitude in individuals with TOF was significantly greater than individuals with normal cardiac morphology (p = 0.013) and SVP (p = 0.005). The mean QRS duration in individuals with normal cardiac morphology was significantly smaller than individuals with TOF (p = 0.0001) and SVP (p = 0.006). Also the mean QRS duration in female was significantly smaller than male (p = 0.03). There were no statistically significant differences in the mean R/T ratio, QTc interval, Tpeak-end duration between subgroups, six postures and three lead (p > 0.05). Conclusion: Postures, electrodes location and cardiac morphologies have impact on the surface ECG morphological components which may have to be considered while designing sensing algorithm of monitoring devices and specifically SICD.